Studies on Food, Health and Environmental Perspectives In Mulberry (Morus Spp.) – A Review (Journal of Bio-Science, 2021)
Mulberry is a very hard and quickly developing plant belongs to the family of Moraceae. The leaf of mulberry is exclusively utilized for feeding and rising of the silkworm (Bombyx mori) for the production of silk yarn. It is evaluated that mulberry silk contributes around 90% of the total worldwide raw silk production that contributed to socio-economic development worldwide. The usage of mulberry leaves as silkworm feed, it is being utilized for food and medicinal purpose also. For instance, the mulberry fruit because of its high nutritive value and flavorful taste is getting significance as important foodstuff. The mulberry bark and wood are likewise helpful for assembling of paper and sports products things. Mulberry is a quickly developing with profound roots, flourish leaves, high protections from pollution, wind, sand, drought, and salinity with strong adaptability and simple cultivation. The broad environmental adaptability of mulberry to light, temperature, water, soil and other normal conditions objectively empowers it to have numerous environmental defensive capacities in water and soil protection, wind tolerance and sand consolidation, water source preservation, and air refreshment. Since earlier, Ayurveda and other literature have claimed the diverse medicinal properties against certain serious diseases e.g. hypertension, hyperglycemia, cancer, arthritis, diabetes and rheumatis, heart disease, inflammation, fever, cough and throat, stomach related disease, unsteadiness, hepatitis etc. The current studies of different pharmacological compounds of medicinal significance present in mulberry plants opens up new avenues of research in the medical science. Under this study briefly described about economic as well as environmental importance of mulberry taking into account different aspects of its role as animal feed, foodstuff, phytomedicine and remediation of polluted soils and atmosphere, etc.J. Bio-Sci. 29(1): 163-179, 2021 (June)